Nutritional support therapy for liver transplantation in an adult-onset type II citrullinemia patient: a case report - Du, Yao; Fu, Yang-Yang; Yue, Yang; Han, Bing; Zhang, Wen-Jie; Yu, De-Cai; Bian, Xiao-Jie (Frontiers in Nutrition, 2024)
Liver transplantation is an effective measure to treat adult-onset type II citrullinemia (CTLN2). Active and effective perioperative nutrition support is a very important treatment for the prognosis of such patients. In this paper, we analyzed the process, results, and outcome of nutritional support therapy in a case of CTLN2, and concluded that the perioperative nutritional support program for CTLN2 patients should be followed prior to surgery:1.because of the prevalence of severe malnutrition in CTLN2 patients, Enteral nutrition (EN) combined with Parenteral nutrition (PN) should be the first choice for nutritional support; 2. daily energy intake should be 35 40 kcal/kg; 3. the nutritional formula should be composed of low-carbohydrates and high medium-chain triglyceride (MCT). Postoperative: initiating EN as soon as possible is recommended to restore intestinal function and adjuvant PN might be taken into consideration in the early stage. The purpose of this case was to provide experience for the development and adjustment of the perioperative nutritional support regimen for CTLN2 patients.